2005
DOI: 10.1021/jf051765z
|View full text |Cite
|
Sign up to set email alerts
|

Curcuma longa L. Constituents Inhibit Sortase A and Staphylococcus aureus Cell Adhesion to Fibronectin

Abstract: The inhibitory activity of Curcuma longa L. (turmeric) rhizome constituents against sortase A, a bacterial surface protein anchoring transpeptidase, from Staphylococcus aureus ATCC 6538p was evaluated. The activity of the isolated compounds (1-4) was compared to that of the positive control,p-hydroxymecuribenzoic acid (pHMB). The biologically active components of C. longa rhizome were characterized by spectroscopic analysis as the curcuminoids curcumin (1), demethoxycurcumin (2), and bisdemethoxycurcumin (3). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(95 citation statements)
references
References 33 publications
5
89
0
1
Order By: Relevance
“…Measurements of bacterial adherence to fibronectin are not a direct measurement of sortase activity, and these assays suffer from pitfalls associated with inhibition of other pathways that also effect adherence (e.g., inhibition of protein synthesis or secretion of polypeptide through the Sec secretion pathway). Curcumin and derivatives from Curcuma longa also inhibited sortase with appreciable activity (IC 50 13-32 g/ml) and potentially prevented adherence to fibronectin (Park et al, 2005). In similar fashion, inhibitors of SrtB from S. aureus were isolated from the bark of the plant R. verniciflua.…”
Section: B Natural Productsmentioning
confidence: 89%
“…Measurements of bacterial adherence to fibronectin are not a direct measurement of sortase activity, and these assays suffer from pitfalls associated with inhibition of other pathways that also effect adherence (e.g., inhibition of protein synthesis or secretion of polypeptide through the Sec secretion pathway). Curcumin and derivatives from Curcuma longa also inhibited sortase with appreciable activity (IC 50 13-32 g/ml) and potentially prevented adherence to fibronectin (Park et al, 2005). In similar fashion, inhibitors of SrtB from S. aureus were isolated from the bark of the plant R. verniciflua.…”
Section: B Natural Productsmentioning
confidence: 89%
“…Physical inhibition using the analogue contributes to preventing bacterial adhesion and dental diseases without any side effects, whereas other drugs, having bactericidal activity, eliminate both pathogenic and beneficial bacteria [21]. In addition, it was previously shown that curcumin did not affect the viability of the S. aureus strain Newman, but inhibited microbial adhesion to cell surfaces, suggesting a role as a potential preventive and curative agent of pathogenic bacterial infections [22]. Therefore, curcumin can be suggested as an improved therapeutic agent showing anti-adherence-based inhibitory mechanisms against S. mutans rather than bactericidal effects.…”
Section: Discussionmentioning
confidence: 99%
“…According to Park et al, Curcuma longa L. components impeded cell membrane-anchored sortase A (SrtA), which is responsible for controlling bacterial adherence to host tissues via interaction with cell-wall matrix proteins, resulting in the inhibition of S. aureus attachment to fibronectin via fibronectin-binding protein [22]. Hence, the use of an SrtA inhibitor such as curcumin was thought to have the potential to eliminate Gram-positive bacterial infections [22]. In addition, S. aureus mutants defective in sortase activity stopped exhibiting surface proteins and initiating infections without the bacterial growth being disturbed [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Turmeric is traditionally known as a blood purifier and is reported to be useful for the common cold, intermittent fevers, afflictions of the liver, indolent ulcer and wound healing. It has been found to possess anti-inflammatory and antioxidant activities and chemopreventive activity for a wide variety of cancers like colon, breast, prostate, esophagus, lung, oral and has potential as an antiviral and antibacterial agent (Mazumder et al, 1995;Anto et al, 1996;Aggarwal et al, 2003;Dorai & Aggarwal, 2004;Duvoix et al, 2005;Olszanecki et al, 2005;Park et al, 2005;Alpers, 2008). Recently Aggarwal and co-workers using a commercially available curcumin mix reported that different analogs of curcumin present in turmeric showed variable anti-inflammatory and antiproliferative activities (Sandur et al, 2007).…”
Section: Discussionmentioning
confidence: 99%